The Use of Social Media in Improving Literacy in Rural Village - Dian Yulie Reindrawati; Ferry Setiawan; Muhammad Ditya Satrianto; Jiwangga Hadi Nata (Universitas Airlangga, 2023)
Background: Social media, in the form of chatting platforms such as WhatsApp and various other social media widely used by Generation Y today, can help to increase literacy and information dissemination in a rural village. With the involvement and contribution of Generation Y, social media has what it takes to improve literacy among people in rural areas, allowing them to obtain information as fast and as precisely as the urban communities do while also making advancements to the area itself. Objective: This study attempts to investigate the use of social media in increasing literacy in eight villages on Madura Island. Method: This study uses a descriptive analysis method with a qualitative approach. Results: The results show that there are still several problems caused by the use of social media among generation Y in making decisions, taking action, behaving, communicating, and socializing. Another issue is that, generally, Generation Y tends to disseminate information directly without checking its veracity. Conclusion: The lack of digital literacy worries many people because it causes the spread of disinformation that threatens the bond of kinship and disperses national unity. Therefore, there is a need for education on how to use social media healthily, provision of rural village and city-level libraries, and the need for attention from clerics, parents, and the government. Keywords: literacy; rural village; social media